Conviviality through creativity: Appealing to the reblog in Tumblr Chat posts. (December 2017) - Vásquez, Camilla; Creel, Samantha
Abstract: Research examining linguistic creativity on the internet has tended to describe various forms of creativity found in online "chats": that is, in technologically-mediated "conversations" taking place synchronously among multiple users interacting in the same virtual space. In this study however, we focus on a different type of "Chat": a newer social media discourse genre, and one that is a built-in feature of popular microblogging platform, Tumblr. These "Chats" are brief, imagined dialogues, posted by a single user. Focusing on a representative selection of 90 popular (i.e., highly reblogged) Chat posts, we illustrate two common strategies used by authors of creative Tumblr Chats: intertextual references to a wide range of cultural phenomena, and those referring to "relatable" first-person situations (i.e., "Me" posts). Our qualitative, interpretive discourse analysis draws on central concepts from Bakhtin, and shows how authors of Chats rely on creative practices, such as polyvocality and double-voicing, in order to produce posts that other Tumblr users are likely to find humorous, and/or relatable.